Occupational Hazards : Migrants and the Economic and Health Risks of COVID-19 in Western Europe - Bossavie, Laurent; Garrote Sanchez, Daniel; Makovec, Mattia; Ozden, Caglar (World Bank, Washington, DC, 2021)
This paper investigates the economic and health risks arising from the COVID-19 pandemic for migrant workers in the European Union. It first assesses migrants’ economic and health vulnerabilities using ex ante measures based on both supply and demand shocks. The analysis finds that immigrants were more vulnerable than native-born workers to both income- and health-related risks, and that this greater exposure stems from the occupations in which migrant workers are concentrated. Migrants work to a greater degree than native-born citizens in occupations that are less amenable to teleworking arrangements, and in economic sectors that experienced greater reductions in demand during the pandemic. This has led to an increase in both their income and employment risks. The paper shows that individual characteristics, such as educational attainment, age, and geographical location, fail to explain the native-migrant gap in exposure to economic and health risks posed by the pandemic. Limited language ability, the concentration of migrants in jobs with labor shortages among native-born workers, and a reliance on immigrant networks to find jobs all appear to play significant roles in migrants’ exposure to pandemic-related risks. Finally, the paper finds that actual job losses in 2020, the first year of the pandemic, are highly correlated with ex-ante vulnerabilities: immigrant workers experienced significantly higher rates of job losses, which partly originates from their greater concentration in non-teleworkable jobs. Ex-ante vulnerabilities, however, only explain part of the migrant-native gap in job losses that followed the pandemic and being an immigrant still imposes additional risks.